The Influence of the Problem-Based Learning Model with Wordwall Media and Learning Motivation on Islamic Religious Education Learning Outcomes - Elida Saragih; Amiruddin Siahaan; Ira Suryani (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) instructional model assisted by Wordwall media and learning motivation on students’ learning outcomes in Islamic Religious Education (PAI) at SMP Negeri 1 Namorambe. This research employed a quasi-experimental method with a 2×2 factorial design. The research population consisted of 160 seventh-grade students distributed across several classes, while the sample comprised 60 students, including 30 students in the experimental group and 30 students in the control group. The research instruments included a learning outcomes test and a learning motivation questionnaire. Data were analyzed using a two-way Analysis of Variance (ANOVA). The results indicated that (1) there was a significant difference in learning outcomes between students taught using the PBL model assisted by Wordwall media and those taught using the Direct Instruction model, (2) there was a difference in learning outcomes between students with high and low learning motivation, and (3) there was an interaction between the instructional model and learning motivation on students’ PAI learning outcomes. These findings demonstrate that the implementation of the Wordwall-assisted PBL model is effective in improving students’ learning outcomes and motivation in Islamic Religious Education.